Dust accumulation due to anthropogenic impact induces anatomical and photochemical changes in leaves of Centranthus ruber growing on the slope of the Vesuvius volcano. (13th February 2019) - De Micco, V.; Amitrano, C.; Stinca, A.; Izzo, L. G.; Zalloni, E.; Balzano, A.; Barile, R.; Conti, P.; Arena, C.
Abstract: In Mediterranean ecosystems, some natural areas are exposed to severe anthropogenic impact. Especially in summer, the considerable number of tourists visiting such areas, often with vehicles, causes deposition of dust over the vegetation due to formation of powder clouds, also favoured by wind erosion, high temperature, low precipitation and incoherent soil structure. The main aim of this study was to analyse whether the deposition of dust can induce changes in leaf anatomical functional traits and in the efficiency of photosynthetic apparatus in Centranthus ruber, a species widespread in Mediterranean ecosystems. Leaf morpho‐functional traits were quantified in plants growing at sites characterised by high (HD) and low (LD) dust deposition, in periods with high anthropogenic impact. Analyses included quantification of chlorophyll fluorescence emission parameters, photosynthetic pigment concentration as well as stomatal size and frequency, leaf lamina thickness, quantification of intercellular spaces and phenolics in the mesophyll through microscopy. The overall analysis suggested that the different conditions of dust deposition induced different adjustment of morpho‐functional traits in leaves of C. ruber . High dust deposition shielded the leaf lamina, protecting the photosynthetic apparatus from excess light and favoured plant photochemical efficiency. Leaves exposed to low dust deposition showed higher accumulation of phenolic compounds, protecting chloroplast membranes and characterised by high thermal dissipation of excess light. Such adaptive phenomena can affect vegetation dynamics due to possible different species‐specific plant responses, resulting in different plant competitiveness under the limiting conditions of Mediterranean environments.